The Application of LQG Balanced Truncation Algorithm to the Digital Filter Design Problem - Bui, H. H. (Engineering, Technology & Applied Science Research, 2022)
This paper presents a method for using a model reduction algorithm to design low-order digital filters. Designing an IIR digital filter that meets the specifications often leads to a high-order digital filter. To reduce the computation time and increase the response rate of the filter, we need to reduce the order of the high-order digital filter. Applying the LQG balanced truncation algorithm to reduce the demand for high-order digital filters shows that low-order filters can completely replace high-order digital filters. The simulation results show that the use of the LQG balanced truncation algorithm in order to reduce the filter order is correct and efficient.